Congenital Cervical and Vaginal Malformations: Lessons from 42 cases Managed Clinically by a Common Protocol [28Q]. (May 2018) - Pan, Hongxin; Luo, Guangnan
Abstract : INTRODUCTION: To outline the anatomic variations and the clinical management of congenital cervical and vaginal malformations in a cohort of 42 patients in China. METHODS: From January 2008 to January 2017, a total of 42 patients with congenital cervical and vaginal malformations were treated in the department of Gynecology at the 3rd affiliated hospital of Shenzhen University (China). Clinical examinations, magnetic resonance imaging, hormonal profile and laparoscopy were collected. All surgical findings were carefully reviewed to determine the anatomic characteristics of the cervical and vaginal malformations. RESULTS: The mean age at the time of symptom onset was 12.8±1.9 years (range 9-17). The mean time from symptom onset to surgery was 3.4±0.9 years (range 0.1-14). Among the 38 patients, (90.5%) had pelvic endometriosis. Among the 38 patients with pelvic endometriosis, 20 patients had ovarian endometrial cysts. Endometriosis was staged as minimal-mild in 21 and as moderate-severe in 17. Of the 42 patients, 5 underwent hysterectomy during their first surgery and 37 received cervical reconstruction surgery. Among these 37 patients, 25 underwent Luohu III procedure (peritoneal vaginoplasty, trachelectomy and uterus-neovagina anastomosis), 12 underwent Luohu IV procedure (laparoscopic vaginal section and peritoneal vaginoplasty). Of the 37 patients with a preserved uterus, 2 attempted pregnancy up to day, and one woman achieved a successful pregnancy but experienced premature delivery. CONCLUSION: Our study found that cervical and vaginal malformations might be successfully treated by uterovaginal anastomosis under laparoscopy. With appropriate evaluation and individualized management, we believe that a successful treatment and pregnancy outcome might be achieved.